Experimental study on shear behavior of joints in precast concrete segmental bridges. (May 2022) - Zou, Yu; Xu, Dong
Abstract: A new shear key was designed in precast segmental bridges, and 12 full-scale specimens were carried out. The types of shear keys (concrete key, steel shear key, inserted reinforcement key), joint types (dry, epoxied), and the number of shear keys (single-key, double-key represented multi-key) were taken as experimental parameters to study the crack development, failure mode, shear slip, ultimate shear capacity, and residual shear capacity of various joints under direct shear loading. The results showed that the stiffness and shear capacity of the steel shear keyed joints are higher than the concrete keyed joints, and the horizontal prestressed system is more stable than the concrete keyed joints at the moment of cracking. There is a local compressive stress concentration in the inserted reinforcement keyed joint, and the load–displacement curve has a long development course, resulting in the large shear slip when the specimen is damaged, which is not suitable as a shear key. The shear slips of steel shear keyed joints are smaller than the concrete keyed joints and inserted reinforcement keyed joints, just are 0.02 ∼ 0.03 mm. The shear capacity of the double-key is 46.66% higher than that of the single-key of steel shear key dry joint. The shear capacity of steel shear key epoxied joints is increased by 69.68%∼118.33% compared with the dry joints. The steel shear key epoxied joints are a direct shear failure, but the mechanical property is similar to the dry joints after direct shear failure, and the ratio of residual shear capacity to ultimate shear capacity is large. Steel shear key has obvious advantages based on mechanical property, simple manufacture, and convenient construction.